Extreme plasma convection and frictional heating of the ionosphere: ISR observations. Issue 7 (13th July 2017) - Akbari, H.; Goodwin, L. V.; Swoboda, J.; St.‐Maurice, J.‐P.; Semeter, J. L.
Abstract: Extremely elevated ion temperatures observed with the Poker Flat and Resolute Bay incoherent scatter radars in the E and F regions of the polar ionosphere are discussed. Our observations include one‐dimensional, line‐of‐sight ion temperatures ( T i, 1 d ) that at times can rise to up to ∼8000°K. While examining the accuracy of the derived temperatures is difficult due to the several potential sources of error and uncertainty, we find that at altitudes of ∼130–250 km the line‐of‐sight ion temperatures obtained at relatively small aspect angles (for instance, at 22.5° away from the magnetic field direction) are below the expected values for the average or three‐dimensional ion temperatures ( T i ). We find that this difference matches well with the theoretical expectation from anisotropic ion velocity distributions that emerge from polarization elastic scattering collisions between NO + and N2 . These results are therefore the clearest detection of anisotropic ion velocity distributions with the Poker Flat Incoherent Scatter Radar and Resolute Bay Incoherent Scatter Radar facilities. Moreover, at higher altitudes (>∼300 km), where the resonant charge exchange collisions prevail, and for a very high ion temperature event ( T i ∼8000°K), we observe that the incoherent scatter radar (ISR) spectra obtained at large aspect angles (e.g., 55°) look like those expected from non‐Maxwellian plasma. At similar altitudes, the measured one‐dimensional temperatures at an aspect angle of 22.5° are found to exceed the expected values from the frictional heating and resonant charge exchange collisions by about 1000°K. A portion of this offset is thought to reflect the role of Coulomb collisions. Key Points: Ion frictional heating in the high‐latitude ionosphere is studied by using incoherent scatter radars Anisotropic and non‐Maxwellian ion velocity distributions are inferred from PFISR/RISR measurements Effect of Coulomb collisions on the ion distribution function is inferred from the derived ion temperatures